Inclined bite plane: indications and application - Eka Erwansyah; Muhammad Wira Sakti; Nasyrah Hidayati (Makassar Dental Journal, 2020)
Background: The prevalence of malocclusion in Indonesia is about 80% of the population and is a fairly common dental and oral health problem so that treatment of malocclusion from an early age is very important and needed. One of malocclusion treatment for preventing malocclusion is the use of removable orthodontic devices in the form of inclined bite plane. Con-clusion: Inclined bite plane can be made on the orthodontic plate of maxilla and mandible. In the maxilla inclined bite plane can function as a functional appliance in treatment of Class II malocclusion division 1, as a retention device after treatment using twin blocks and in the mandible serves to correct anterior crossbite.